Genome‐wide effect of tetracycline, doxycycline and 4‐epidoxycycline on gene expression in Saccharomyces cerevisiae. Issue 7 (17th August 2020) - Sanchez, Guadalupe; Linde, Samuel C.; Coolon, Joseph D.
Abstract: Tetracycline (Tet) and derivative chemicals (e.g., doxycycline or Dox) have gained widespread recognition for their antibiotic properties since their introduction in the late 1970s, but recent work with these chemicals in the lab has shifted to include multiple techniques in all genetic model systems for the precise control of gene expression. The most widely used Tet‐modulated methodology is the Tet‐On/Tet‐Off gene expression system. Tet is generally considered to have effects specific to bacteria; therefore, it should have few off‐target effects when used in eukaryotic systems, and a previous study in the yeast Saccharomyces cerevisiae found that Dox had no effect on genome‐wide gene expression as measured by microarray. In contrast, another study found that the use of Dox in common cell lines and several model organisms led to mitonuclear protein imbalance, suggesting an inhibitory role of Dox in eukaryotic mitochondria. Recently, a new Dox derivative, 4‐epidoxycycline (4‐ED) was developed that was shown to have less off‐target consequences on mitochondrial health. To determine the best tetracycline family chemical to use for gene expression control in S. cerevisiae, we performed RNA sequencing (RNA‐seq) on yeast grown on standard medium compared with growth on media supplemented with Tet, Dox or 4‐ED. We found each caused dozens of genes to change expression, with Dox eliciting the greatest expression responses, suggesting that the specific tetracycline used in experiments should be tailored to the specific gene(s) of interest when using the Tet‐On/Tet‐Off system to reduce the consequences of confounding off‐target responses.